MRNA COVID-19 Vaccine and Hope to Cure Cancer - Yadav, Ajay Kumar; Gnawali, Suman; Yuan, Gangbiao (Nepalese Journal of Cancer, 2021)
There is hope that cancer patient should benefit from mRNA COVID-19 vaccination. Some of the most advanced candidate vaccines are encapsulated in carriers of lipids, and small liposomes are expected to accumulate in tumor tissue through the enhanced effect of permeation and retention. However, the extent to which solid tumors might take a significant part of the vaccine dose, so it is still unknown. This requires a careful evaluation of these promising vaccines of mRNA COVID-19 managed as carriers of lipids for patients with solid tumors, including a possible revaluation of the assay for optimal protection of this specification and the fragile population.